Lignin-hydroxyapatite / biomass-based composite aerogel as well as preparation and application thereof
By preparing lignin-hydroxyapatite/biomass-based composite aerogel, the problems of flammability and insufficient mechanical properties of biomass-based aerogels are solved, and the flame retardant and thermal insulation properties are improved. It is suitable for a wide range of Application scenarios and provide low-cost process solutions.
Patent Information
- Application Number
- CN202411442603.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Biomass-based aerogels have problems such as flammability, insufficient mechanical properties, and easy to absorb and soften moisture in the field of thermal insulation, and commonly used flame retardants are toxic and harmful.
The preparation method of lignin-hydroxyapatite/biomass-based composite aerogel is adopted, and sodium alginate is combined as the gel matrix by in-situ release method, lignin as the structural enhancer and macromolecular carbon-forming agent, hydroxyapata As a crosslinking agent and flame retardant, a flame retardant biomass composite aerogel is prepared by freeze-drying and hydrophobic modification techniques.
It has achieved improved mechanical properties of aerogels, excellent flame retardant properties, and is not easy to absorb moisture, broadened its application scenarios, and provided low-cost and simple process solutions, suitable for thermal insulation fields.
Smart Images

Figure HDA0005086753080000011 
Figure HDA0005086753080000012 
Figure HDA0005086753080000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of flame retardant and heat insulating materials, and specifically relates to a lignin-hydroxyapatite / biomass-based composite aerogel and preparation and application thereof. Background Art
[0002] With the continuous progress of science and technology and the rapid development of society, the process of industrialization is accelerating, and the population density is also rising rapidly, resulting in a continuous increase in energy consumption. In this context, saving resources and coping with energy shortages have become important measures to achieve sustainable development. Thermal insulation materials can effectively reduce heat loss and improve energy utilization efficiency. They are widely used in thermal insulation of building walls, cold chain transportation, underground pipelines, new energy vehicles and other fields. However, most thermal insulation materials are mainly petroleum-based materials, which are non-renewable and will produce a large amount of toxic and harmful gases when burned, which seriously pollutes the environment and threatens people's life, health and safety. Aerogel has gradually entered the public's field of vision due to its excellent performance and application prospects, and has become a hot research topic in the field of thermal insulation in recent years. Among them, biomass aerogel has attracted the interest of more and more researchers due to its wide source of raw materials, non-toxic, environmentally friendly, renewable, and low cost. However, its flammability limits its application in the fields of flame retardancy and thermal insulation. Therefore, the flame retardant research on biomass aerogel is of great significance.
[0003] Alginate is a byproduct of extracting iodine and mannitol from kelp or sargassum of brown algae. It is an important component of algae such as seaweed. It mainly exists in the cell wall and plays a supporting and strengthening role on the cell wall. There are a large number of hydroxyl groups on the chain of alginate. Because the hydrogen bonds between the chains are too strong, it is difficult to dissolve in water, which makes it not conducive to use. Therefore, the most common salt to neutralize alginate is its sodium salt. Alginate is composed of β-D-mannuronic acid (M block) and α-L-guluronic acid (G block) randomly arranged through 1,4-glycosidic bonds. The G fragment has a certain rigidity and can be stably combined with divalent metal ions. The M fragment has a certain flexibility and hardly participates in ionic cross-linking. The gelation ability and molecular characteristics of alginate can be expressed by the M / G ratio. At present, commercially available alginate only comes from algae. There are abundant algae resources such as brown algae and algae in rivers and oceans. Alginate substances exist in large quantities in nature, so the raw materials of sodium alginate (SA) are cheap and easy to obtain.
[0004] Lignin is the most abundant aromatic polymer in nature, with a wide range of sources and huge output. Every year, a large amount of lignin by-products are produced by the pulp and paper industry and the bioethanol industry. Most of the lignin by-products are simply incinerated or discharged into rivers and oceans for treatment, resulting in extremely low utilization of lignin, causing environmental pollution and waste of resources. Lignin contains abundant carbon atoms in its chemical structure, which can be used as a filler in some materials, which can greatly improve the mechanical properties of the materials and provide a carbon source to form an isolating carbon layer during the combustion process of the materials. As an aromatic polymer, lignin's own rigid structure can also improve the mechanical properties of aerogels. In short, lignin has great application prospects in the field of biomass aerogels.
[0005] At present, there are still some problems in using biomass-based aerogel as thermal insulation material: mechanical properties and flame retardant properties cannot be achieved at the same time, toxic and harmful flame retardants are used, and it is easy to absorb moisture and soften. Therefore, it is necessary to design an aerogel with wide application scenarios, simple process, low cost, and excellent flame retardant and thermal insulation properties. Summary of the invention
[0006] In order to solve the problems of biomass-based aerogels being generally flammable, having insufficient mechanical properties, and softening upon moisture absorption, improve the various properties of aerogels, and broaden the application scenarios of biomass-based aerogels, the primary purpose of the present invention is to provide a method for preparing lignin-hydroxyapatite / biomass-based composite aerogels.
[0007] The method of the present invention is based on an in-situ release method, using a composite system of hydroxyapatite (HAP) and gluconolactone (GDL), with sodium alginate as a gel matrix, lignin as a structural reinforcing agent and a macromolecular carbon forming agent, hydroxyapatite as a cross-linking agent and a flame retardant to release a calcium source and a phosphorus source, and a flame retardant biomass composite aerogel is obtained by simple freeze drying. The aerogel is hydrophobically modified to form a super-hydrophobic aerogel. The sodium alginate and lignin of the present invention are both biomass resources, with abundant output and a wide range of sources, and the preparation method is simple in process and easy to be applied in large-scale production. Relative to the traditional in-situ release method, the composite system of hydroxyapatite (HAP) and gluconolactone (GDL) does not produce gas, does not produce small pores inside the gel, has a certain improvement in the overall performance of the aerogel, and has good application prospects in the fields of heat preservation and thermal insulation.
[0008] Another object of the present application is to provide a lignin-hydroxyapatite / biomass-based composite aerogel prepared by the above method.
[0009] Another object of the present invention is to provide an application of the above-mentioned lignin-hydroxyapatite / biomass-based composite aerogel.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] A method for preparing a lignin-hydroxyapatite / biomass-based composite aerogel comprises the following steps:
[0012] (1) mixing hydroxyapatite, lignin, sodium alginate and an alkaline solution to obtain a composite solution;
[0013] (2) adding the calcium ion regulator solution dropwise to the composite solution of step (1), mixing evenly and then standing to gel, and freeze-drying to obtain a sodium alginate / lignin / hydroxyapatite composite aerogel;
[0014] (3) The sodium alginate / lignin / hydroxyapatite composite aerogel was hydrophobically modified by chemical vapor deposition to obtain hydrophobic lignin-hydroxyapatite / biomass-based composite aerogel.
[0015] Preferably, the alkaline solution in step (1) is at least one of a sodium hydroxide solution and a potassium hydroxide solution; the concentration of the alkaline solution is 0.03 to 0.06 mol / L; more preferably 0.05 mol / L.
[0016] Preferably, the ratio of hydroxyapatite to alkaline solution in step (1) is 0.3-0.9 g:80 mL; more preferably 0.9 g:80 mL.
[0017] Preferably, the composite solution in step (1) is obtained by the following method: adding hydroxyapatite to an alkaline solution, mixing evenly, adding lignin and sodium alginate, and mixing evenly again to obtain a composite solution.
[0018] More preferably, after the hydroxyapatite is added to the alkaline solution, a homogenizer is used to mix the mixture at 40-60°C.
[0019] More preferably, after adding lignin and sodium alginate, the mixture is stirred at 40-60° C. for 1-2 hours to mix them evenly.
[0020] Preferably, the lignin in step (1) is at least one of alkali lignin, enzymatic lignin, lignin sulfonate and solvent lignin; more preferably, it is lignin sulfonate, and most preferably, it is sodium lignin sulfonate.
[0021] Preferably, in step (1), the mass ratio of sodium alginate to lignin is 1:0.5-1, more preferably 1:1; the mass ratio of hydroxyapatite to sodium alginate is 0-0.3:1, wherein the hydroxyapatite is not 0; further preferably, the mass ratio of hydroxyapatite to sodium alginate is 0.1-0.3:1; most preferably 0.3:1.
[0022] Preferably, the concentration of the calcium ion regulator solution in step (2) is (0.02-0.06) g / mL; more preferably 0.04 g / mL.
[0023] Preferably, the mass ratio of the calcium ion regulator to hydroxyapatite in step (2) is 8:(2-9), more preferably 8:9 or 8:2.25.
[0024] Preferably, the calcium ion regulator in step (2) is at least one of gluconolactone, gluconic acid and lactic acid; more preferably, it is gluconolactone.
[0025] Preferably, the mixing time in step (2) is 3 to 10 minutes, more preferably 5 minutes.
[0026] Preferably, the step (2) of allowing the gel to stand is carried out in a mold.
[0027] Preferably, the time for leaving the gel to stand in step (2) is 3 to 6 hours.
[0028] Preferably, before freeze-drying in step (2), the gel is first refrigerated at -20 to -30°C for more than 12 hours or frozen with liquid nitrogen to complete freezing of the gel.
[0029] Preferably, the freeze-drying temperature in step (2) is from -50°C to room temperature, and the time is 12 to 48 hours, more preferably 48 hours.
[0030] Preferably, the modifier used for the hydrophobic modification in step (3) is at least one of methyltrichlorosilane and methyltrimethoxysilane; more preferably methyltrichlorosilane.
[0031] Preferably, the ratio of the modifier used for the hydrophobic modification in step (3) to the sodium alginate / lignin / hydroxyapatite composite aerogel is 1 mL: 2-3 g.
[0032] Preferably, the time for the hydrophobic modification in step (3) is 6 to 24 hours; more preferably 12 hours.
[0033] The above preparation method produces a lignin-hydroxyapatite / biomass-based composite aerogel.
[0034] The above-mentioned lignin-hydroxyapatite / biomass-based composite aerogel is used in the field of flame retardancy and thermal insulation.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0036] 1. The present invention is based on the in-situ release method, with huge raw material output and low cost, and a simple preparation process. Gluconolactone is added to a system in which hydroxyapatite and sodium alginate are evenly mixed, stimulating the insoluble hydroxyapatite to release calcium ions. Since hydroxyapatite is evenly dispersed in the mixed system during the preparation process, the sodium alginate chains of each part can bind to an equal amount of calcium ions, and compared with the traditional in-situ release method, no gas is generated, and no pores are generated in the hydrogel to destroy the overall structure, which can provide a better thermal insulation effect.
[0037] 2. The aerogel obtained by the present invention has excellent mechanical properties, thermal insulation properties and lightness, and still has excellent smoke suppression performance. As a flame retardant and heat insulating material, it has excellent comprehensive performance. The phosphate part in hydroxyapatite is equivalent to a phosphorus flame retardant, which can effectively improve the flame retardant effect of the aerogel.
[0038] 3. The lignin in the present invention has a large number of rigid phenylpropane units and a high carbon content. The introduction of the lignin into the aerogel can effectively improve the mechanical properties of the aerogel, which is of great help to the formation of the carbon layer, and will not affect the overall lightness and smoke suppression of the aerogel. At the same time, it opens up new ways for the resource utilization of lignin and realizes the transformation of waste into treasure.
[0039] 4. The hydrophobically modified aerogel of the present invention will not absorb moisture and deliquesce due to excessive air humidity, which broadens the application scenarios of aerogels; the flame-retardant gel constructed will provide valuable data and reference for the subsequent design of such aerogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the design idea of the sodium alginate / sodium lignin sulfonate / hydroxyapatite composite aerogel of the present invention.
[0041] Figure 2 Schematic diagram of fluidity of Comparative Example 1, Comparative Example 3 and Example 3.
[0042] Figure 3 These are SEM images of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 3.
[0043] Figure 4 Schematic diagram of aerogel in flower-bearing embodiment 3 and schematic diagram of weight compression embodiment 3.
[0044] Figure 5 These are the thermogravimetric curves of Comparative Example 2, Comparative Example 3 and Example 3.
[0045] Figure 6 This is a schematic diagram of human body load-bearing in Example 3.
[0046] Figure 7 These are the stress-strain curves of Comparative Example 2, Comparative Example 3 and Example 3.
[0047] Figure 8 1 and 2 are thermal conductivity diagrams of Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 1, Example 2 and Example 3.
[0048] Fig. 9 These are infrared camera images of Comparative Example 3 and Example 3 after the heating plates are heated.
[0049] Fig.10 Schematic diagram of vertical combustion of Comparative Example 4 and Example 4.
[0050] Fig.11 The contact angle diagram and dye immersion state diagram of Example 3 (before hydrophobic modification) and Example 6 (after hydrophobic modification) are shown.
[0051] Fig.12 The thermal conductivity comparison performance of Comparative Example 5, Comparative Example 6, Example 5 and Example 7 is shown.
[0052] Fig.13 It is a comparison chart of the cumulative smoke production of Comparative Example 2 and Example 3.
[0053] Fig.14 It is a comparison chart of the cumulative smoke production of Comparative Example 5, Comparative Example 6, Example 5 and Example 7. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0055] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0056] Example 1
[0057] Weigh 0.3g of hydroxyapatite powder (HAP) and add it to 80mL of 0.05mol / L NaOH solution at 50℃. After being evenly dispersed with a homogenizer, weigh 3g of sodium lignin sulfonate (LS) and stir it evenly to dissolve it in the hydroxyapatite solution. Continue to add 3g of sodium alginate (SA) and continue stirring for 1.5h to make the solution completely mixed. Weigh 0.8g of glucose lactone (GDL) and dissolve it in 20mL of deionized water. Under continuous stirring, slowly drip 20mL of GDL solution into the sodium alginate / lignin solution, stir for about 4 to 5min until the solution is evenly mixed, then pour the mixed solution into a cylindrical mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, it is frozen with liquid nitrogen, and after freezing, it is placed in a vacuum freeze dryer at a temperature of -50℃ and dried for 48h to obtain S3L3H0.3G0.8 composite aerogel.
[0058] Example 2
[0059] Weigh 0.6g of hydroxyapatite powder (HAP) and add it to 80mL of 0.05mol / L NaOH solution at 50℃. After being evenly dispersed with a homogenizer, weigh 3g of sodium lignin sulfonate (LS) and stir it evenly to dissolve it in the hydroxyapatite solution. Continue to add 3g of sodium alginate (SA) and continue stirring for 1.5h to make the solution completely mixed. Weigh 0.8g of glucose lactone (GDL) and dissolve it in 20mL of deionized water. Under continuous stirring, slowly drip 20mL of GDL solution into the sodium alginate / lignin solution, stir for about 4 to 5min until the solution is evenly mixed, then pour the mixed solution into a cylindrical mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, it is frozen with liquid nitrogen, and after freezing, it is placed in a vacuum freeze dryer at a temperature of -50℃ and dried for 48h to obtain S3L3H0.6G0.8 composite aerogel.
[0060] Example 3
[0061] Weigh 0.9g of hydroxyapatite powder (HAP) and add it to 80mL of 0.05mol / L NaOH solution at 50℃. After being evenly dispersed with a homogenizer, weigh 3g of sodium lignin sulfonate (LS) and stir it evenly to dissolve it in the hydroxyapatite solution. Continue to add 3g of sodium alginate (SA) and continue stirring for 1.5h to make the solution completely mixed. Weigh 0.8g of glucose lactone (GDL) and dissolve it in 20mL of deionized water. Under continuous stirring, slowly drip 20mL of GDL solution into the sodium alginate / lignin solution, stir for about 4 to 5min until the solution is evenly mixed, then pour the mixed solution into a cylindrical mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, it is frozen with liquid nitrogen, and after freezing, it is placed in a vacuum freeze dryer at a temperature of -50℃ and dried for 48h to obtain S3L3H0.9G0.8 composite aerogel.
[0062] Example 4
[0063] Weigh 0.9g of hydroxyapatite powder (HAP) and add it to 80mL of 0.05mol / L NaOH solution at 50℃. After being dispersed evenly with a homogenizer, weigh 3g of sodium lignin sulfonate (LS) and stir it evenly to dissolve it in the hydroxyapatite solution. Continue to add 3g of sodium alginate (SA) and continue stirring for 1.5h to make the solution completely mixed. Weigh 0.8g of glucose lactone (GDL) and dissolve it in 20mL of deionized water. Under continuous stirring, slowly drip 20mL of GDL solution into the sodium alginate / lignin solution and stir for about 4 to 5min until the solution is evenly mixed. Then pour the mixed solution into a 1×1×10cm long strip mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, it is placed in a refrigerator at a temperature of -30°C and frozen for 24 hours. After being frozen solid, it is placed in a vacuum freeze dryer at a temperature of -50°C and dried for 48 hours to obtain a 1×1×10 cm long strip of S3L3H0.9G0.8 composite aerogel.
[0064] Example 5
[0065] 0.45g of hydroxyapatite powder (HAP) was weighed and added to 80mL of 0.05mol / L NaOH solution at 50℃. After being dispersed evenly with a homogenizer, 3g of sodium lignin sulfonate (LS) was weighed and stirred to dissolve evenly in the hydroxyapatite solution. 3g of sodium alginate (SA) was added and stirred for 1.5h to make the solution completely mixed. 0.8g of glucose lactone (GDL) was weighed and dissolved in 20mL of deionized water. Under continuous stirring, 20mL of GDL solution was slowly dripped into the sodium alginate / lignin solution and stirred for about 4 to 5min until the solution was evenly mixed. Then the mixed solution was poured into a cylindrical mold and allowed to stand for 3h to form a hydrogel. After the hydrogel was formed, it was frozen with liquid nitrogen, and after being frozen solid, it was placed in a vacuum freeze dryer at -50℃ and dried for 48h to obtain S3L3H0.45G0.8 composite aerogel.
[0066] Example 6
[0067] Weigh 0.9g of hydroxyapatite powder (HAP) and add it to 80mL of 0.05mol / L NaOH solution at 50℃. After being evenly dispersed with a homogenizer, weigh 3g of sodium lignin sulfonate (LS) and stir it evenly to dissolve it in the hydroxyapatite solution. Continue to add 3g of sodium alginate (SA) and continue stirring for 1.5h to make the solution completely mixed. Weigh 0.8g of glucose lactone (GDL) and dissolve it in 20mL of deionized water. Under continuous stirring, slowly drip 20mL of GDL solution into the sodium alginate / lignin solution, stir for about 4 to 5min until the solution is evenly mixed, then pour the mixed solution into a cylindrical mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, it is frozen with liquid nitrogen, and after freezing, it is placed in a vacuum freeze dryer at a temperature of -50℃ and dried for 48h to obtain S3L3H0.9G0.8 composite aerogel. Then, 1 mL of methyltrichlorosilane was put into the bottle and placed into a beaker together with 2 g of aerogel. After sealing, a bottle-in-bottle device was formed and placed in a fume hood for 12 hours. After completion, it was taken out and placed in a vacuum oven to remove excess methyltrichlorosilane to obtain the silane-modified S3L3H0.9G0.8 composite aerogel.
[0068] Example 7
[0069] 0.45g of hydroxyapatite powder (HAP) was weighed and added to 80mL of 0.05mol / L NaOH solution at 50℃. After being evenly dispersed with a homogenizer, 3g of sodium lignin sulfonate (LS) was weighed and stirred to dissolve evenly in the hydroxyapatite solution. 3g of sodium alginate (SA) was added and stirred for 1.5h to make the solution completely mixed. 1.6g of gluconolactone (GDL) was weighed and dissolved in 20mL of deionized water. Under continuous stirring, 20mL of GDL solution was slowly dripped into the sodium alginate / lignin solution and stirred for about 4 to 5min until the solution was evenly mixed. Then the mixed solution was poured into a cylindrical mold and allowed to stand for 3h to form a hydrogel. After the hydrogel was formed, it was frozen with liquid nitrogen, and after being frozen solid, it was placed in a vacuum freeze dryer at a temperature of -50℃ and freeze-dried for 48h to obtain S3L3H0.45G1.6 composite aerogel.
[0070] Comparative Example 1
[0071] Weigh 1.5g of sodium lignin sulfonate (LS) and add it to 100mL of 0.05mol / L NaOH solution at 50°C. Stir with a stirring paddle until it is evenly dissolved, then add 3g of sodium alginate (SA) and continue stirring for 1.5h to mix the solution completely. Then pour the mixed solution into a cylindrical mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, freeze it with liquid nitrogen, and after freezing, put it in a vacuum freeze dryer at -50°C and dry it for 48h to obtain S3L1.5 composite aerogel.
[0072] Comparative Example 2
[0073] Weigh 3g of sodium lignin sulfonate (LS) and add it to 100mL of 0.05mol / L NaOH solution at 50°C. Stir with a stirring paddle until it is evenly dissolved, then add 3g of sodium alginate (SA) and continue stirring for 1.5h to mix the solution completely. Then pour the mixed solution into a cylindrical mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, freeze it with liquid nitrogen, and after freezing, put it in a vacuum freeze dryer at -50°C and dry it for 48h to obtain S3L3 composite aerogel.
[0074] Comparative Example 3
[0075] At 50°C, 3 g of sodium alginate (SA) was added to 100 mL of 0.05 mol / L NaOH solution and stirred for 1.5 h to mix the solution thoroughly. The mixed solution was then poured into a cylindrical mold and allowed to stand for 3 h to form a hydrogel. After the hydrogel was formed, it was frozen with liquid nitrogen and then placed in a vacuum freeze dryer at -50°C for 48 h to obtain S3 aerogel.
[0076] Comparative Example 4
[0077] At 50°C, add 3g of sodium alginate (SA) to 100mL of 0.05mol / L NaOH solution and stir continuously for 1.5h to mix the solution thoroughly. Then pour the mixed solution into a 1×1×10cm long strip mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, put it in a refrigerator at -30°C for 24 hours. After freezing, put it in a vacuum freeze dryer at -50°C for 48h to get a 1×1×10cm long strip S3 aerogel.
[0078] Comparative Example 5
[0079] Weigh 0.45g of calcium carbonate powder (CaCO3) and add it to 80mL of 0.05mol / L NaOH solution at 50℃. After being evenly dispersed with a homogenizer, weigh 3g of sodium lignin sulfonate (LS) and evenly dissolve it in the calcium carbonate solution. Continue to add 3g of sodium alginate (SA) and continue stirring for 1.5h to mix the solution completely. Weigh 1.6g of glucose lactone (GDL) and dissolve it in 20mL of deionized water. Under continuous stirring, slowly drip 20mL of GDL solution into the sodium alginate / lignin solution, stir for about 4 to 5min until the solution is evenly mixed, then pour the mixed solution into the mold and let it stand for 3h to form a hydrogel. After the hydrogel is formed, it is frozen with liquid nitrogen, and after being frozen solid, it is placed in a vacuum freeze dryer at a temperature of -50℃ and freeze-dried for 48h to obtain S3L3(CaCO3)0.45G1.6 composite aerogel.
[0080] Comparative Example 6
[0081] Under magnetic stirring at room temperature, weigh 3g of sodium lignin sulfonate and add it to 80mL, 0.05mol / L NaOH solution. After stirring and dissolving, weigh 0.45g of calcium carbonate powder and evenly disperse it in the lignin solution. Then add 3g of sodium alginate and stir for 5h to make the solution completely mixed. Weigh 1.6g of gluconolactone and dissolve it in 20mL of deionized water, and shake it gently to make it completely dissolved. Under stirring, use a dropper to add 20mL of gluconolactone solution to the sodium alginate / lignin solution, continue stirring for 1.5min, pour the sol into the mold, and let it stand for 12h to form a hydrogel. Freeze the hydrogel in a -20℃ refrigerator for more than 24h. After freezing, put it in a -50℃ freeze dryer and freeze-dry it for 48h to obtain S3L3(CaCO3)0.45G1.6 aerogel.
[0082] Example Effect Description
[0083] Figure 1 The design concept of the sodium alginate / sodium lignin sulfonate / hydroxyapatite composite aerogel of the present invention is shown.
[0084] Figure 2 The fluidity diagram of Comparative Example 1, Comparative Example 3 and Example 3. Inverting the solution in the bottle verifies that the sol precursor has strong cross-linking behavior. At a certain concentration, the S3 and S3L1.5 sols are very viscous and have poor fluidity. When the bottle is turned 180°, they will flow down along the bottle wall because there is no cross-linking behavior inside. The prepared S3L3H0.9G0.8 composite hydrogel will stick firmly to the bottom of the bottle. These phenomena can simply prove that a cross-linking reaction has occurred inside the hydrogel.
[0085] Figure 3The SEM images of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 3 are shown. It can be seen that the aerogels frozen by liquid nitrogen direction all contain rich pore structures, while the sodium alginate aerogels without sodium lignin sulfonate mainly present a porous structure of stacked sheets, with poor mechanical strength, soft pore walls, and easy to be deformed by extrusion. With the addition of sodium lignin sulfonate, the hydrogen bonding effect between macromolecules gradually increases, and sodium lignin sulfonate becomes one of the components of the skeleton structure, providing strong support for the skeleton, and the structure of the aerogel becomes denser, which is manifested in that the pore size of the aerogel gradually decreases, and the cross-section of the measured aerogel presents a vertical pore structure, and the pore wall strength gradually increases. After adding HAP, the composite aerogel presents a denser porous honeycomb structure with pores extending in all directions.
[0086] Figure 4 Schematic diagram of aerogel in flower-carrying Example 3 and schematic diagram of weight compression Example 3 show that the composite aerogel can be placed on an open flower without deforming the flower and can easily carry the weight of a 500g weight, indicating that the prepared S3L3H0.9G0.8 composite aerogel has the characteristics of light weight and high strength.
[0087] Figure 5 The thermogravimetric curves of Comparative Example 2, Comparative Example 3 and Example 3 show that as the temperature increases, all samples present similar three stages: the first weight loss stage is mainly at 50-100°C, which may be due to the high porosity and large specific surface area of the sample, which makes it easy to adsorb free water in the air. The evaporation of free water in the initial stage of heating will cause a part of the mass loss; the second stage occurs at 200-300°C, which is the main weight loss stage, which may be the cracking of the sodium alginate / sodium lignin sulfonate skeleton; at higher temperatures, the small molecular substances produced by the pyrolysis of the aerogel in the previous stage are further degraded to form the final residual carbon. S3 aerogel begins to decompose rapidly at around 200°C, and the weight loss rate reaches the maximum at around 250°C. When the temperature exceeds 900°C, the remaining mass is only about 13%. Compared with S3 aerogel, the composite aerogel with LS added has a certain increase in the temperature at which the mass loss is 10%, indicating that the addition of LS is helpful to improve the thermal stability of the material. After adding HAP, it can be observed from the DTG curve that the maximum thermal degradation rate of the composite aerogel is significantly reduced, and the temperature corresponding to the maximum thermal decomposition rate is increased, indicating that HAP effectively improves the thermal stability of the aerogel.
[0088] Figure 6 This is a schematic diagram of human body load-bearing in Example 3, where 8 samples are placed in both the left and right figures. It shows that the prepared S3L3H0.9G0.8 composite aerogel can bear the weight of an adult without serious deformation, and has the potential to be applied in practical places.
[0089] Figure 7The stress-strain curves of Comparative Example 2, Comparative Example 3 and Example 3 show that all aerogels show similar characteristics in the test, and have three characteristic stages: a linear deformation stage with low strain (0-5%), a platform stage with gradually increasing stress when the strain is moderate (5-10%), and a densification stage with a sharp increase in stress when the strain is high (>50%). The compression modulus of S3 aerogel is 0.69MPa, and after adding an equal amount of sodium lignin sulfonate, the compression modulus of S3L3 aerogel increases to 2.7MPa, which is about 3.9 times larger, indicating that sodium lignin sulfonate is added to sodium alginate aerogel as a structural enhancer, which can effectively improve the mechanical strength of the composite aerogel. After adding HAP, the mechanical strength of the aerogel is further increased, and the strength of the S3L3H0.9G0.8 composite aerogel reaches 6.34Mpa.
[0090] Figure 8 The thermal conductivity diagrams of Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 1, Example 2 and Example 3 show that with the increase of sodium lignin sulfonate, the thermal conductivity of the material first increases and then decreases. This is because the addition of sodium lignin sulfonate has a certain effect on the solid-phase thermal conduction of the aerogel skeleton structure and has an enhancing effect on heat transfer. However, due to the rigid characteristics of lignin itself, the pore wall of the aerogel changes from soft and tortuous to flat and orderly, reducing the gas-phase thermal conduction of the aerogel pore structure. The influence of gas-phase thermal conduction is greater than that of solid-phase thermal conduction, and ultimately manifests as a decrease in thermal conductivity, which is consistent with the results of scanning electron microscopy. Similarly, the addition of HAP will also increase the volume density of the material, resulting in an increase in thermal conductivity, but it is still at a low level, and the aerogel still has good thermal insulation performance.
[0091] Fig. 9 The infrared camera images of the heating plates of Comparative Example 3 and Example 3 after heating. The aerogel was placed on a 200°C heating plate for a heating experiment and an infrared camera was used to record the temperature change on its surface. The infrared heat distribution on its surface was observed to explore the thermal insulation properties of the composite aerogel and the effect of its thickness on the thermal insulation properties. The temperature on the surface of the aerogel first increased and then stabilized. Compared with the S3 aerogel, the upper surface temperature of the S3L3H0.9G0.8 composite aerogel of the same height was finally 73°C after heating for 10 minutes, which is much lower than the 93°C of the sodium alginate aerogel. The above results show that the composite aerogel has excellent thermal insulation properties.
[0092] Fig.10It is a schematic diagram of vertical combustion of Comparative Example 4 and Example 4. It can be observed from the figure that both gels do not produce dripping and open flames when burning, however, S3 aerogel will carbonize, shrink and spread upward when burning. After adding HAP, the carbonization rate of S3L3H0.9G0.8 is further slowed down, and the deformation of the gel is relatively small. The gel with the addition of HAP is equivalent to adding a phosphorus-based flame retardant, which produces phosphorus radicals and phosphorus-nitrogen radicals at high temperatures, which can capture H· and OH· produced by combustion and terminate the chain reaction during the combustion process. This shows that the addition of HAP greatly improves the fire resistance of sodium alginate aerogel.
[0093] Fig.11 The contact angle diagram and dye immersion state diagram of Example 3 (before hydrophobic modification) and Example 6 (after hydrophobic modification) are shown. The results show that the water contact angle of S3L3H0.9G0.8 before modification is only 12.49°, and after hydrophobic modification, the water contact angle of S3L3H0.9G0.8 composite aerogel is as high as 157°, and can still reach 152° after being placed for 5 days. It can also be known from the immersion state of the dye that the unmodified composite aerogel dye penetrates into the interior of the aerogel, and after modification, the dye stays on the surface in the form of droplets. After hydrophobic modification, the prepared aerogel can adapt to humid environments, greatly expanding the application range of aerogels.
[0094] Fig.12 The thermal conductivity comparison performance of Comparative Example 5, Comparative Example 6, Example 5 and Example 7. The results show that the thermal conductivity value of Example 5 < Comparative Example 5 < Comparative Example 6 < Comparative Example 7. The reduction of thermal conductivity is of great help to the improvement of thermal insulation performance, which may be due to the binary sustained release system of gluconolactone and hydroxyapatite and the reaction of sodium alginate can make the gel network more uniform, and will not produce CO2 gas to destroy the integrity of the aerogel structure. After the pores become smaller and more uniform, the gas phase turbulence is low, the thermal conductivity is reduced, and the thermal insulation performance is improved.
[0095] Fig.13 It is a comparison chart of the cumulative smoke production of comparative example 2 and example 3. The results show that after adding hydroxyapatite using the binary sustained-release system, the smoke production is greatly reduced, and a good smoke suppression effect is achieved.
[0096] Fig.14 The figure is a comparison chart of the cumulative smoke production of Comparative Example 5, Comparative Example 6, Example 5 and Example 7. The results show that the smoke production of Example 5 and Example 7 are significantly lower than that of Comparative Example 6 and Comparative Example 7, and the smoke production of Comparative Example 6 is also significantly lower than that of Comparative Example 7. The use of water bath heating and homogenizer dispersion can effectively enhance the uniformity of hydroxyapatite inside the gel, and the smoke suppression effect of hydroxyapatite is better than that of calcium carbonate, which has a certain effect on reducing smoke production.
[0097] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a lignin-hydroxyapatite / biomass-based composite aerogel, characterized in that: The following steps are involved: (1) mixing hydroxyapatite, lignin, sodium alginate and an alkaline solution to obtain a composite solution; (2) adding the calcium ion regulator solution dropwise to the composite solution of step (1), mixing evenly and then standing to gel, and freeze-drying to obtain a sodium alginate / lignin / hydroxyapatite composite aerogel.
2. The preparation method according to claim 1, characterized in that: The sodium alginate / lignin / hydroxyapatite composite aerogel was hydrophobically modified by chemical vapor deposition to obtain hydrophobic lignin-hydroxyapatite / biomass-based composite aerogel.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of sodium alginate to lignin is 1:0.5-1; the mass ratio of hydroxyapatite to sodium alginate is 0-0.3:1, wherein the mass ratio of hydroxyapatite is not 0; The mass ratio of the calcium ion regulator to the hydroxyapatite in step (2) is 8:(2-9); The lignin in step (1) is at least one of alkali lignin, enzymatic lignin, lignin sulfonate and solvent lignin; In step (2), the calcium ion regulator is at least one of gluconolactone, gluconic acid and lactic acid.
4. The preparation method according to claim 1, characterized in that: The alkaline solution in step (1) is at least one of a sodium hydroxide solution and a potassium hydroxide solution; the concentration of the alkaline solution is 0.03 to 0.06 mol / L; The ratio of hydroxyapatite to alkaline solution in step (1) is 0.3-0.9 g: 80 mL; The concentration of the calcium ion regulator solution in step (2) is 0.02-0.06 g / mL.
5. The preparation method according to claim 2, characterized in that: The modifier used for the hydrophobic modification is at least one of methyltrichlorosilane and methyltrimethoxysilane; The ratio of the modifier used for the hydrophobic modification to the sodium alginate / lignin / hydroxyapatite composite aerogel is 1 mL: 2-3 g; The time for the hydrophobic modification in step (3) is 6 to 24 hours.
6. The preparation method according to claim 1, characterized in that: The composite solution in step (1) is obtained by the following method: adding hydroxyapatite to an alkaline solution, mixing evenly, adding lignin and sodium alginate, and mixing evenly again to obtain a composite solution; After the hydroxyapatite is added to the alkaline solution, a homogenizer is used to mix it uniformly at 40-60°C; After adding lignin and sodium alginate, stir at 40-60° C. for 1-2 hours to make them uniformly mixed.
7. The preparation method according to claim 1, characterized in that: The mixing time in step (2) is 3 to 10 minutes; The gelling time in step (2) is 3 to 6 hours; Before freeze drying in step (2), the gel is first refrigerated at -20 to -30°C for more than 12 hours or frozen with liquid nitrogen to freeze the gel completely; The freeze-drying temperature in step (2) is from -50°C to room temperature, and the time is 12 to 48 hours.
8. The preparation method according to claim 3, characterized in that: The lignin in step (1) is lignin sulfonate; The mass ratio of sodium alginate to lignin in step (1) is 1:1; The mass ratio of hydroxyapatite to sodium alginate in step (1) is 0.1-0.3:1; The mass ratio of the calcium ion regulator to hydroxyapatite in step (2) is 8:9 or 8:2.25; In step (2), the calcium ion regulator is gluconolactone.
9. A lignin-hydroxyapatite / biomass-based composite aerogel prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the lignin-hydroxyapatite / biomass-based composite aerogel according to claim 9 in the field of flame retardancy and heat insulation.
Citation Information
Patent Citations
Hydrophobic lignin / cellulose aerogel oil-water separation material as well as preparation method and application thereof
CN112480464A
High-strength sodium alginate / lignin flame-retardant aerogel as well as preparation method and application thereof
CN114835942A
Preparation method of clay-based composite hydrogel for solar seawater desalination
CN115651274A
Method for manufacturing hydrophobic aerogel heat insulating material and use thereof
JP2021172567A
Cited By
Preparation method of inorganic nanofiber composite diaphragm, diaphragm and lithium battery
CN120016081A